Penggunaan Medium Tanam dan Volume Pemberian Air pada Budidaya Tanaman Pakcoy (Brassica chinensis L.) Sistem Vertikultur - Multi Hermiza; Ardian Ardian; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aimed to determine the effect of the use of some of the embedding medium and the volume of water provision and get the best combination for growth and pakcoy crop is cultivated with vertikultur system. This research has been conducted in the greenhouse of Faculty of Agriculture, University of Riau, Pekanbaru, for 4 months from April to July 2017, This study uses a randomized block design (RAK) factorial. The first factor was embedding medium consisting of 3 levels, Medium base: rice husk ash: sawdust ash M1=1:0:0, M2=1:1:0, M3=1:0:1 The second factor was the volume of water consists of 5 levels, V1=100 ml,V2=150 ml, V3=200 ml, V4=250 ml, V5 =300 ml/day. Parameters those observed were: plant height, leaf number, root volume, fresh weight and marketable crop for consumption. The results of further analysis of variance using Duncan's multiple range test at the 5 % level. Interaction of planting medium composition and the water volume did not give significant effect on plant height, leaf number, root volume, fresh weight and the weight of the marketable plant for consumption. Marketable crop for consumption very strongly positively correlated with plant height and fresh weight as well as being correlated with the number of leaves. Keywords: Pakcoy, Medium planting, Water volume, Vertikultur.